Leading holistic improvement with Lean Six Sigma 2.0 - Snee, Ronald D.; Hoerl, Roger Wesley (Pearson Education, 2018)
We live in a very different world from 1987 when Six Sigma was first introduced by Motorola, and from the early 2000s when the first books on Six Sigma and Lean Six Sigma deployment appeared. How should one think about continuous improvement in a modern world? Is Lean Six Sigma the best approach to take for all problems, including large, complex, unstructured problems, such as climate change or the Millennial Development Goals? The authors argue that a different paradigm is needed to take continuous improvement to a new level in the world in which we now find ourselves. Snee and Hoerl refer to this paradigm as Holistic Improvement, and suggest Lean Six Sigma 2.0, the next version of Lean Six Sigma, as the best methodology based on this paradigm. Holistic improvement incorporates a diverse array of improvement methods, beyond Lean and Six Sigma, to ensure that organizations can apply the most relevant improvement method to a specific problem. Leading Holistic Improvement with Lean Six Sigma 2.0 is the only book on the market that addresses the developments that have occurred in the last 15 years, and also provides a way to address these developments. These developments include the rapid growth of globalization, the recognition of the importance of large, complex, unstructured problems, the rise of Data Science as a discipline, and the growing importance of risk management in a world beset by terrorism and computer hacking of confidential information. This book includes learnings from Snee and Hoerl's extensive use of Lean Six Sigma in improving process and organizational performance, and also their research on the topics that include two previous books and more than twenty published articles on the subject.